The influence of enterprise risk management disclosure and intellectual capital disclosure on the value of companies with an independent board of commissioners as moderation variables - Ledy Setiawati; Indra Suyoto Kurniawan; Ibnu Abni Lahaya (Faculty of Economics and Business Mulawarman University, 2022)
The purpose of this study is to test and analyze the influence of enterprise risk management disclosure and intellectual capital disclosure on company values as well as independent board of commissioner variables in moderating the influence of enterprise risk management disclosure and intellectual capital disclosure limited to company value. The data used in the research is sourced from secondary data, namely non-financial company data of basic and chemical sub-financial sub-industry. The sample screening method uses purposive sampling method with a total of 61 companies and 4 years so that the data observed amounted to 244. The analysis tool used is Moderating Regression Analysis (MRA) by using SPSS version 21 as software to process data. The results showed that enterprise risk management disclosure has a significant effect on the value of the company while Intellectual capital disclosure has no significant effect on the value of the company and the independent board of commissioners is able to strengthen the influence of enterprise risk management disclosure and intellectual capital disclosure on the value of the company.